Investigating Social Vulnerability to Extreme Heat: Heat Islands and Climate Shelters in Urban Contexts: The Case of Bologna - Elisa Maccabiani; Munazza Usmani; Riccardo Nanni; Maurizio Napolitano (ISPRS International Journal of Geo-Information)
In this article we present three instruments: (1) a social vulnerability to extreme heat index to identify the areas of a city (and populations thereof) more vulnerable to extreme heat due to climate change (heat islands); (2) a new overall fragility index that incorporates social vulnerability to extreme heat as well as socioeconomic indicators; and (3) a climate shelter index (CSI) to identify areas within a city that can provide relief from extreme heat based on green and blue solutions. We elaborated these three indexes to measure social vulnerability to extreme heat in the municipality of Bologna, which serves as this article’s case study. By analyzing the connections between social vulnerability to extreme heat and several socio-demographic variables in Bologna, we found that a decrease in income is significantly correlated with an increase in social vulnerability to extreme heat in urban contexts. A comparison between our new overall fragility index and the existing index adopted by the municipality of Bologna (Indice di fragilità, Comune di Bologna) showed that about 75% of the statistical areas observed are worse off when social vulnerability to extreme heat is also considered. Considering social vulnerability to extreme heat shows vulnerabilities in a city (here: Bologna) that the pre-existing index did not consider. These findings and our new indexes can support the Bologna administration (and other local administrations) in addressing the consequences of climate change for their most vulnerable residents.